Are analysts effective speaking tubes? Evidence from site visits. Issue 2 (8th January 2023) - Wang, Jun; Wu, Chongfeng
ABSTRACT: This study examines the association between analysts' site visits and stock price crash risk using a dataset of Chinese firms listed on the Shenzhen Stock Exchange (SZSE) from 2012 to 2019. We find that analysts' site visit frequency is positively associated with future stock price crash risk, and the positive association is primarily driven by the firms that analysts keep silent on. Furthermore, we confirm that analysts' silence is associated with negative news about firms' fundamentals. We also show that the effect of analysts' silence on crash risk is more pronounced when analysts face conflicts of interest, when firms have poorer information transparency, and when firms have fewer alternative information channels. Overall, our findings shed light on the dark side of analysts' site visits.